ANÁLISE DA UTILIZAÇÃO ENDODÔNTICA DO GEL PRODUZIDO À BASE DO EXTRATO HIDROGLICÓLICO DO PERICARPO DE Punica granatum L. (ROMÃ) CONTRA Enterococcus faecalis: EFEITO ANTIMICROBIANO E TOXICIDADE - Schreiner, Fabiane (2016)
Due to endodontic treatment failure, virulence and increase of antibiotic resistant microorganisms bacterial infections had a greater incidence. Plant extracts are promising resources in the control of biofilms and can be considered a new way to prevent and / or treat infections. Among these natural products, there is the Punica granatum L. (pomegranate),which features bioactive compounds such as flavonoids and phenols. Objective: To analyze, in vitro and ex vivo, the antibacterial effect of auxiliary substances based on Punica granatum L. (pomegranate) against Enterococcus faecalis. Method: After developed the hydroglycolic peel extract of Punica granatum L. , agar diffusion tests, determination of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) and analysis of toxicity (lethality in microcrustacean - Artemia salina were performed. With this data gel with hydroglicolic extract of P. granatum pericarp (0.5 g/mL) were developed and tested in agar diffusion, as auxiliary substance of endodontic instrumentation and as intracanal medication in infected dentin with E. faecalis by counting colony forming units per milliliter (cfu/mL) in three experimental times. Results: The MIC was 0.5 g/ml and P. granatum gel at this concentration showed 8 mm inhibition zones against E. faecalis. The P. granatum gel reduced 96% in cfu/mL after instrumentation (p = 0.005), with evidence of effectiveness for use as an intracanal medication (p = 0.047), reducing contamination by 65%. The brine shrimp mortality rate was 42%, with an LC50 of 62.7 mg/ml, being a sligthy toxic extract. Conclusion: The pomegranate gel 0.5 g/ml was effective against E. faecalis and represents promising proposal in Endodontics.